If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(8+4x)=7(2+6x)
We move all terms to the left:
7(8+4x)-(7(2+6x))=0
We add all the numbers together, and all the variables
7(4x+8)-(7(6x+2))=0
We multiply parentheses
28x-(7(6x+2))+56=0
We calculate terms in parentheses: -(7(6x+2)), so:We get rid of parentheses
7(6x+2)
We multiply parentheses
42x+14
Back to the equation:
-(42x+14)
28x-42x-14+56=0
We add all the numbers together, and all the variables
-14x+42=0
We move all terms containing x to the left, all other terms to the right
-14x=-42
x=-42/-14
x=+3
| h-35=3-7 | | 3y-5=16y+8 | | -5=-(m-6) | | 2/3b+5=20-b= | | 3x2+10=2x | | 0.25(-b+2)=12 | | 15w+0=40 | | -3(1-5x)=1(4x+2) | | 9=11x+24 | | 6(x-2)=9(x+7x) | | |u-15|+2=8 | | -0.65x+0.45x=5.5 | | 6-2r=-3r+6r+1 | | 57b−52=6b−57 | | v=4/33.14117.649 | | 180=5x+2+x-2 | | 18(x/9+2x/2=1/3) | | 5n-3=7n-2 | | 34+90+2y=180 | | v=3.1442.875 | | 5x+8+2x=-48 | | 3(60-1y)+0.75y=135 | | 14x-19=47 | | 27^x+8=9^2x-7 | | -0.3x=6.9 | | A/10(w+8)=18 | | 3(1+p)=-5(p+5) | | 32-6b-5=7.25 | | 6x-26=56-6x | | 19x+3=9x+16+6x+15 | | 13x-2(x+4)=10 | | -6(-1+4x)=6(2x+7) |